Identificação biométrica de pessoas via características dos seios paranasais obtidas de tomografias computadorizadas - Souza Júnior, Luis Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Biometric identification of people in the forensic field is constantly being studied to facilitate and improve the identification methods through the evaluation of several structures that can be used as biometric features. The paranasal sinuses, bone cavities present in the skull, have high individuality and permanence and can be used in forensic biometric systems. The X-rays and Computed Tomography are modalities of medical examinations used for the digital representation of the paranasal sinuses. X-rays images as a tool to obtain characteristics of the paranasal sinuses are highly applicable in the related works, however, in this imaging modality, some disadvantages, such as low quality resolution, make these structures harder to acquire. With computed tomography representation, a new evaluation can be performed to obtain the paranasal sinuses features, knowing that this exam modality generates an image sequence with higher quality, making the paranasal sinuses segmentation and feature extraction simpler, intuitive and precise, facilitating its use in biometric recognition systems. The objective of this master’s dissertation was the development of a new human identification method that uses paranasal sinuses structures as biometric features, obtained from computed tomography images. This method proposes significant advances, specially on the segmentation and features extraction stages, once the segmentation of the paranasal sinuses structures is performed automatically. The characteristics proposed for the feature descriptors are based on the region and shape of the paranasal structures. The experimental results obtained from a database composed by 310 computed tomography images presented that the automatic method proposed in this dissertation showed 88.52% of frontal sinuses segmentation and 79.30% of correct maxillary sinuses segmentation using the KAPPA coefficient. Relative to the persons identification, the proposed method presented in the best case 8.99% of EER. Therefore, in this master’s dissertation, it was concluded that: the face sinuses, and in particular the frontal sinuses, can be used with success for the forensic human identification; for the human identification based on the frontal sinuses the shape descriptors are more efficient than the region descriptors, while that for the human identification based on maxillary sinuses, the shape descriptors do not presented high discrimination performance and; it is possible to automate the frontal and maxillary sinuses segmentation process using computed tomography images.

A identificação biométrica de pessoas na área forense está em constante estudo para facilitar e melhorar as maneiras de identificação mediante a avaliação de diversas estruturas que podem ser utilizadas como características biométricas. Os seios paranasais, cavidades ósseas presentes no crânio, apresentam alta individualidade e permanência, podendo ser utilizados em sistemas biométricos forenses. As maneiras de representação digital dos seios paranasais são modalidades de exames médicos, conhecidos como raios-X e tomografia computadorizada. As imagens de raios-X como ferramentas para obtenção de características dos seios paranasais apresentam alta aplicação nos trabalhos correlatos, entretanto, nesta modalidade de imagem, algumas desvantagens, como a baixa qualidade de resolução dificultam a identificação dos seios paranasais. Com a tomografia computadorizada, uma nova avaliação pode ser realizada para a obtenção das características dos seios paranasais, visto que esta modalidade de exame gera uma sequência de imagens com qualidade superior, tornando a segmentação e extração de características dos seios paranasais mais simples, intuitiva e precisa, facilitando seu uso em sistemas de reconhecimento biométrico. O objetivo desta dissertação foi desenvolver um novo método de identificação humana utilizando estruturas dos seios paranasais, obtidas de imagens de tomografia computadorizada, como características biométricas. Este método propõe avanços significativos principalmente nas etapas de segmentação e extração de características, uma vez que a segmentação das estruturas dos seios paranasais é realizada de forma automática. As características propostas como descritores são baseadas nas regiões e nas formas das estruturas dos seios paranasais. Resultados experimentais obtidos sobre uma base de dados contendo 310 imagens de tomografia computadorizada mostraram que o método automático proposto nesta dissertação obteve taxa de segmentação medida pelo Coeficiente KAPPA igual a 88,52% na segmentação dos seios frontais e 79,30% na segmentação dos seios maxilares. Com relação à identificação de pessoas, o método proposto obteve, no melhor caso, 8,99% de taxa de erro igual (EER). Assim, nesta dissertação de mestrado concluiu-se que: os seios da face podem ser utilizados com êxito para a identificação forense de pessoas, em particular os seios frontais; que os descritores de forma para os seios frontais são mais efetivos do que os descritores de região para a identificação de pessoas, enquanto que para os seios maxilares, os descritores de forma não apresentam alto valor de discriminação entre os indivíduos e; que é possível automatizar o processo de segmentação dos seios frontais e maxilares utilizando-se imagens de tomografia computadorizada.
Biometric human identification by means of paranasal sinuses features obtained from computed tomographys
Keywords: Biometrics; Paranasal sinuses; Computed tomography; Forensics identification; Biometria; Tomografia computadorizada; Seios paranasais; Identificação forense